Pengaruh Kepemilikan Institusional, Komisaris Independen, dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Perusahaan BUMN Yang Terdaftar Dalam Bursa Efek Indonesia - Mahardika Catur Putriwana Malik; Agatha Christy Situru (Insan Cita Bongaya Research Journal, 2023)
The aim of the research is to examine the influence of Institutional Ownership, Independent Commissioners and Financial Performance on Company Value. The population in this study are state-owned companies registered with the Indonesian Stock Exchange. The sampling technique uses purposive sampling technique. The data sources used are secondary data and multiple linear regression analysis methods. The research results show that Institutional Ownership influences Company Value, Independent Commissioners influence Company Value, and dividend policy has no effect on Company Value.